2004
DOI: 10.1111/j.1399-3038.2004.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and asthma in overweight children at 12 years of age

Abstract: Obesity is suggested as a risk factor for asthma, but the mechanisms are unclear. The relationship between obesity and asthma has not been considered in children born with very low-birth weight (VLBW). We hypothesized that overweight was a contributing factor for asthma in VLBW children, and that leptin and leptin-associated cytokines might play roles in overweight-related asthma. Seventy-four VLBW and 64 normal birth weight (NBW) children participated in a 12-yr follow up study assessing asthma and allergy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 42 publications
4
73
3
7
Order By: Relevance
“…(24) Mai et al studied the association between serum leptin levels and asthma in overweight and non-overweight children in Sweden. (25) They found that serum leptin levels were twice as high in overweight children with asthma than in overweight children without asthma. Among non-overweight children, however, the authors found serum leptin levels to be similar between children with and without asthma.…”
Section: Resultsmentioning
confidence: 99%
“…(24) Mai et al studied the association between serum leptin levels and asthma in overweight and non-overweight children in Sweden. (25) They found that serum leptin levels were twice as high in overweight children with asthma than in overweight children without asthma. Among non-overweight children, however, the authors found serum leptin levels to be similar between children with and without asthma.…”
Section: Resultsmentioning
confidence: 99%
“…19 Furthermore, immunomodulatory effects of obesity, mediated by adipocytokines including leptin, have also been postulated to underlie asthma in obese children. 20,21 However, because not all obese children develop asthma, these factors may play a role, but do not explain the higher predisposition for pulmonary morbidity in some, but not other, obese children. Therefore, there is need for better identification of key molecules and biomarkers that may predict asthma development among at-risk obese children.…”
Section: Mechanisms Linking Obesity and Asthmamentioning
confidence: 99%
“…96 To maintain homeostasis, the proinflammatory effect of leptin is offset by antiinflammatory adipokines, including adiponectin, and omentin and the related antiinflammatory cytokine IL-10. [97][98][99] Clinical studies have demonstrated elevated leptin 21 and reduced adiponectin levels in obese children 33, 100 compared with nonobese children with asthma, suggesting that obesityinduced changes in the systemic adipocytokine milieu may underlie asthma in children. 101 (Table 2).…”
Section: Obesity-mediated Inflammation and Asthmamentioning
confidence: 99%
“…A study by Mai and colleagues supports this theory; they observed higher levels of serum leptin in overweight children than in children of normal weight, and in addition, the levels of leptin in overweight children with current asthma were higher (albeit not significantly) than levels in children without current asthma despite similar BMI. 30 However, our study does not allow us to draw any conclusions regarding the biological mechanisms underlying the association between overweight and asthma.…”
Section: Discussionmentioning
confidence: 66%